(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND Hepatitis C virus (HCV) infections in Switzerland are mainly related to intravenous drug use. Since 2017, all patients with chronic hepatitis C can be treated with direct-acting antivirals (DAAs) irrespective of fibrosis stage. In March 2019, the Federal Office of Public Health (FOPH) published guidelines for HCV management in people who use drugs. To achieve HCV elimination by 2030, 80% treatment uptake is necessary. AIM To evaluate the benefit of interferon-based and interferon-free HCV treatment in patients on opioid agonist therapy (OAT) and monitor HCV elimination, a 2-year study commissioned by the FOPH and conducted within the Swiss Association for the Medical Management in Substance Users (SAMMSU) cohort was performed. METHODS Since 2014, the SAMMSU cohort has recruited OAT patients from eight different centres throughout Switzerland. In addition to yearly follow up, cross-sectional data were collected at the time-points 1 May 2017, 1 May 2018 and 1 May 2019. HCV treatment uptake, adherence and success, as well as reinfection rates, the effect of early versus late treatment and the efficacy of the “treatment-as-prevention” approach were analysed. RESULTS Between 1 May 2017 and 1 May 2019, the number of patients enrolled into the SAMMSU cohort increased from 623 to 900: 78% were male, the median age was 45 years, 81% had ever used intravenous drugs, 13% were human immunodeficiency virus (HIV) positive and 66% were HCV antibody positive. HCV treatment up to 2012 was exclusively interferon based (maximum 21 patients/year) and since 2016 exclusively interferon free (102 patients in 2017). Treatment success increased from 57% (112/198; interferon based) to 97% (261/268; interferon free) irrespective of cirrhosis or prior non-response to interferon. Simultaneously, treatments became shorter and better tolerated in the interferon-free era, resulting in fewer preterm stops (17% vs 1%) and adherence problems (9% vs 2%). Between 2015 and 2018, the proportion of patients with no/mild fibrosis (F0/F1) at first HCV treatment increased from 0% to 61%. Earlier treatment reduced the duration of infectiousness. Between 1 May 2017 and 1 May 2019, the proportion of chronic hepatitis C patients ever treated increased from 62% (198/321) to 80% (391/490). In parallel, the HCV-RNA prevalence among HCV antibody-positive patients declined from 36% (139/385) to 19% (113/593). The reinfection rate after successful treatment was 2.7/100 person-years. The number of HCV first diagnoses per year decreased from >20 up to 2015 to <10 in 2017 and 2018. CONCLUSION With nearly 100% DAA treatment success and a low reinfection rate, treatment uptake directly translates into a reduction of HCV-RNA prevalence. Eighty percent treatment uptake is feasible in OAT patients, and adherence and treatment success are not worse than in other populations. Duration of infectiousness and thus HCV transmission can be reduced by early detection and treatment of chronic hepatitis C.